Pancreatitis kills cysts: A phenomenon that illustrates the potential role of immune activation in premalignant cyst ablation - Walsh, Leonard T.; Moyer, Matthew T. (Endoscopy International Open, 2020)
Background and study aims Pancreatic cystic lesions are being increasingly recognized on cross-sectional imaging and mucinous premalignant cysts represent one of the most prevalent types. Endoscopic ultrasound (EUS)-guided chemoablation offers a safe and minimally invasive ablation approach yet with limited efficacy. Patients who develop acute pancreatitis as a complication of chemoablation with alcohol however experience ablation rates up to 100 %. This evidence suggests that recruitment of the body’s immune system may represent an avenue to significantly increase the efficacy of EUS-guided chemoablation. Here we illustrate this immune-mediated tumor killing phenomenon through a case presentation at our institution.